ANALISIS KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN SEMARANG (STUDI PENGAMATAN DI BAGIAN UMUM) - Navik, Ilma; Lestari, Hesti; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
This study aims to determine the relationship between discipline and employee capabilities with the performance of employees in Semarang District Secretariat (Observation Study in the General Section). The population of as many as 69 employees to as many as 35 samples taken employees.Hypothesis testing using the formula Kendall's tau-b to determine the relationship between each independent variable with the dependent variable, and the analysis of the Kendall concordance (W) to determine the relationship of the independent variables together on the dependent variable.Analysis of the relationship between two (2) independent variable discipline (X1) and the ability of employees (X2) with employee performance (Y), either alone or taken together show the following:1. Relations discipline with the employee's performance and significant positive correlation with the value of 0.372, which means that the relationship is positive, but weak, whereas the significance level of the coefficient of 0.030, which means its value is below 0.05 (5%), which means significantly.2. Employee relations skills with the performance of employees with a positive and significant correlation value of 0.353, which means that the relationship is positive but weak, whereas the significance level of the coefficient of 0.035, which means its value is below 0.05 (5%), which means significantly.3. A positive relationship together - collaboration between discipline variable (X1) and the ability of employees (X2) with employee performance variable (Y) with the correlation value of 0.244, which means that the relationship is positive but weak, whereas the significance level of the coefficient of 0.000, which means well below 0.05 (5%), which means significantly.